Breeding soundness evaluation in crossbred bulls: Can testicular measurements be used as a tool to predict ejaculate quality? - VIJETHA, B T; RAJAK, S K; LAYEK, S S; KUMARESAN, A; MOHANTY, T K; CHAKRAVARTY, A K; GUPTA, A K; ASLAM M K, MUHAMMAD; MANIMARAN, A; PRASAD, SHIV (The Indian Journal of Animal Sciences, 2014)
The present study analyzed the relationship between testicular biometry and initial semen quality in Karan Fries (KF) crossbred bulls. Data on semen production traits of KF bulls (n=32) spread over a period of 3 years were analyzed to find out the ejaculate rejection rate (ERR). The scrotal circumference (SC), testicular length (TL) and testicular width (TW) were measured once in a month and 16 ejaculates were collected from bulls (n=24). The relationship between different testicular measurements and the ejaculate quality was studied. To study if the testicular biometry parameters differ between good and poor semen producing bulls, based on the semen evaluation, the bulls were ranked into good and poor. Our study revealed that ERR in KF bulls varied from 23.02 to 100%, with the average of 52.46%. The SC was significantly negatively correlated (–0.459) with ERR. Between good and poor bulls, there was no difference in SC, TL and TW, however, testicular mass (TM) and testicular volume (TV) differed significantly. From the results of the study, it may be inferred that that SC had a positive relationship with initial semen quality, but combination of SC, TL, TW, TV and TM may yield superior results for the selection of crossbred bulls.